Energy and economic impact of the new Dubai municipality green building regulations and potential upgrades of the regulations - Abu-Hijleh, Bassam (2019)
Dubai government has shown great interest in integrating sustainable principles into the different phases of construction. In 2011, the Green Buildings Regulations and Specification (GBRS) were issued to form a market shift toward a Green Economy for Sustainable Development. This research is to evaluate the effectiveness of the different building regulations in effect in Dubai, as well as assessing the benefits of raising the bar to the PassivHaus (PH) standards. The thermal impact of the building envelope on the energy performance and cooling load reduction are the core focus of this study. Hence, a case study villa in Jumeirah Park was selected to be analyzed, modified and simulated using the IESVE energy modeling software. The impact of each building envelope element was assessed individually based on current Dubai regulations, as well as the PH specifications. Cooling load savings of 5.9%, 8.67%, 1.55%, 11% and 20% were achieved when using the new Dubai GBRS glazing, roof, floor, green roof specifications and the best combination of all three elements, respectively. Upgrading the design to the PH specifications resulted in a 48% reduction in the cooling load. The addition of Monocrystalline and Thin Film PV systems reduced the electricity consumption from the grid by 73% and 57%, respectively. Enhancing HVAC efficiency was also identified as a potential approach to save on the electricity used to provide the required cooling load, around 30% reduction when increasing the HVAC′ EER from the minimum current value of 8.53–12.2 (at T1 conditions). The economic analysis showed that the only viable solutions, based on simple payback period analysis, are upgrades to the floor (case 17 and SPP of 6.5 years) and windows (case 24 and SPP of 7 years). The results of this study could help in future development of Dubai's GBRS based on the technical, as well as the economic, viability of upgrading different building elements. .